Attitudes towards and experiences with economic incentives for engagement in HIV care and treatment: Qualitative insights from a randomized trial in Kenya. - Sarah Iguna; Monica Getahun; Jayne Lewis-Kulzer; Gladys Odhiambo; Fridah Adhiambo; Lina Montoya; Maya L Petersen; Elizabeth Bukusi; Thomas Odeny; Elvin Geng; Carol S Camlin (PLOS Global Public Health)
Growing literature has shown heterogenous effects of conditional cash incentives (CCIs) on HIV care retention. The field lacks insights into reasons why incentives impact various patients in different ways-differences that may be due to variations in psychological and social mechanisms of effect. A deeper understanding of patients' perceptions and experiences of CCIs for retention may help to clarify these mechanisms. We conducted a qualitative study embedded in the ADAPT-R trial (NCT#02338739), a sequential multiple assignment randomized trial (SMART) that evaluated economic incentives to support retention in HIV care among persons living with HIV (PLHIV) initiating antiretroviral therapy in Kenya. Participants who attended their scheduled clinic visits received an incentive of approximately $4 each visit. Interviews were conducted between July 2016 and June 2017 with 39 participants to explore attitudes and experiences with economic incentives conditional on care engagement. Analyses revealed that incentives helped PLHIV prioritize care-seeking by alleviating transport barriers and food insecurity: "I decided to forgo [work] and attend clinic […] the voucher relieved me". Patients who borrowed money for care-seeking reported feeling relieved from the burden of indebtedness to others: "I borrow with confidence that I will pay after my appointment." Incentives fostered their autonomy, and enabled them to support others: "I used the money to buy some clothes and Pampers for the children." Participants who were intrinsically motivated to engage in care ("my life depends on the drugs, not the incentive"), and those who mistrusted researchers, reported being less prompted by the incentive itself. For patients not already prioritizing care-seeking, incentives facilitated care engagement through alleviating transport costs, indebtedness and food insecurity, and also supported social role fulfillment. Conditional cash incentives may be an important cue to action to improve progression through the HIV treatment cascade, and contribute to better care retention.